Reduzir retrabalhos e perdas operacionais e financeiras do processo de produção de dublagem e legendagem - Reis, Dennis Marques (2019)
Through this work, and according to the approach of Marcondes, Miguel, Franklin and Perez (2017), a problem solution was presented for a dubbing and subtitling company. The company sought greater efficiency in its production process and for that, it was necessary to reduce its rework and consequently to reduce operational and financial losses. The market in which it operates has undergone changes due to the growth of content in entertainment platforms. Due to market needs and the complexity of execution of the projects among the different types of products delivered to customers. To better understand the problems, interviewing and brainstorming techniques were applied, as well as SWOT analysis and process design to identify the main problems to be addressed. After checking the issues that impacted the organization's objectives, the focus on addressing the problems was focused on processes, people and technology. The proposals elaborated as solution were: the redesign of the process, the automation of systems and meritocracy by the performance of people. In this sense, proposals for solutions and their respective action plans were presented to the organization, with technological innovation within its segment and considering the redesign of the process and the automation of activities with applicability in its implementation. The front of people tried to implement a pilot program of performance evaluation and awards. The applications are present in the intervention performed in the company have brought relevant results in the process performance and a breakthrough with the technology applied. There was a reduction in the delivery times of products to customers and a decrease in the costs inherent in the production process. The amount of rework was better monitored and reduced significantly. The presentation of the result of the intervention of this work can be shared and replicated, serving as the basis for decisions of other companies of different segments.